Identification and classification of interested parties of the construction enterprise. - Podoinitsyn, S.; Zapiechna, Y. (Ways to Improve Construction Efficiency, 2023)
According to theorists and practitioners, the main factor in the emergence of problems in relations with stakeholders is a lack of understanding of stakeholder management processes. In other words, it is a lack of management of stakeholders’ expectations. First of all, this is due to the fact that, more often than not, there is a lack of understanding about which stakeholders surround the enterprise, what they want (their circle of interests), and what influence they can exert to achieve their own goals. Identification and classification of interested parties is one of the foundations of the enterprise’s management activities, aimed at minimizing the occurrence of conflict situations with individual stakeholders, as well as at protecting relations between partners, taking the desired place on the construction market, and obtaining a positive reputation. In turn, the idea of interested parties introduced into the enterprise’s system of life creates certain values and features both for the enterprise and for the stakeholders themselves. In the article, based on the study and analysis of literary sources, the concept of "interested parties" is defined, the main groups of stakeholders are formed, and the circles of interested parties specific to the construction industry are highlighted. Having identified these groups of interested parties in the future, there is an opportunity to understand their direct interests, expectations and influence on the enterprise, which will provide an opportunity to choose the development vector of the construction organization. The theory of interested parties is considered, in which, according to the research of scientists, it is proposed to divide stakeholders into categories both according to their functional characteristics and to classify them depending on the interests and power they possess. A number of different criteria for the identification of stakeholders developed by Ukrainian and foreign experts, as well as those criteria based on the AA 1000 SES standard of interaction with interested parties, are proposed. The importance of identification and classification of stakeholders of the construction enterprise in order to take into account their characteristics and expectations is characterized and substantiated.